Personality Of Aron Ralston In Danny Boyle's 127 Hours Movie (2010): A Psychoanalytic Perspective - Fitriana, Mita (2012)
This study attempts to explore the personality of the major character on his live. The objective of the research is to analyze the major character based on its structural elements and psychoanalytic perspective. In analyzing psychoanalytic aspect, the researcher applied the theory of psychoanalysis proposed by Sigmund Freud. The object of the study is 127 Hours movie that was directed by Danny Boyler. There are two types of data sources, first is the primary data source that is taken from 127 Hours movie that was directed by Danny Boyler. Second is the secondary data sources that are taken from other sources such as the director's bibliography, information about the movie, and other relevant information that supports the analysis. In analyzing this study, the writer uses descriptive qualitative analysis. It concerns with the structural elements of the movie and psychoanalytic perspective. The results of the research show that, first, Danny Boyler creates the characters in such a way that he can relate those characters with the idea he wants to imply through his work. Based on structural element analysis, all of the elements can relate to one another comprising solid unity. Second, Danny Boyler wants to show how Aron Ralston to control his ego, in one incredible situation to get something biggest after that.